Room-temperature tuning of magnetic anisotropy in samarium-thulium orthoferrites - Bolletta, Juan Pablo (2022)
Rare-earth orthoferrites (RFeO3) provide a flexible playground for magnetic materials design, combining the magnetic properties arising from complex interactions between R3+ and Fe3+ cations within the robust framework of the perovskite structure. The most important magnetic property common to most orthoferrites is a spin reorientation transition in which the magnetic moments of Fe3+ cations rotate with respect to a crystallographic axis. SmFeO3 is unique among orthoferrites due to its high-temperature spin reorientation. It is possible to tune the spin reorientation transition to occur at room temperature by replacing Sm with Tm in the Sm0.70Tm0.30FeO3 perovskite. In this study, we show how small changes in composition in the Sm1-xTmxFeO3 (x=0.30-0.50) series provide a high degree of control over the magnetic properties. This work also offers a rather unusual look into the magnetic structure of a samarium-based perovskite by means of neutron powder diffraction, which was made possible by using Sm152. The combination of these results and magnetization measurements allowed the construction of the magnetic phase diagram of the series.